2017
DOI: 10.1016/j.surfcoat.2017.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical rutile and anatase formation on PEO surfaces

Abstract: A highly porous surface with a high crystalline content and resultant photocatalytic activity is ensured through the process of plasma electrolytic oxidation on pure titanium. In the present study the morphology, crystallinity and photocatalytic activity of plasma electrolytic oxidized TiO2-surfaces were investigated. The surfaces were prepared in acidic and alkaline electrolytes over an applied voltage range between 50 V and 300 V to optimize the crystalline and photocatalytic properties. Scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…The formation of the porous layer is mainly determined by the number and intensity of discharges that occur above the breakdown voltage V B . Previous research has shown that V B depends on the ion conductivity of the electrolyte, which is a function of the electrolyte concentration [13,27]. In accordance with the theory, V B is smaller in 12.9 M than in 1 M (compare, e.g., the I transients for 12.9 M and 1 M in Figure 1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The formation of the porous layer is mainly determined by the number and intensity of discharges that occur above the breakdown voltage V B . Previous research has shown that V B depends on the ion conductivity of the electrolyte, which is a function of the electrolyte concentration [13,27]. In accordance with the theory, V B is smaller in 12.9 M than in 1 M (compare, e.g., the I transients for 12.9 M and 1 M in Figure 1).…”
Section: Discussionsupporting
confidence: 87%
“…Galvanostatic, potentiostatic and potentiodynamic operating modes are commonly applied [7] and have been compared with respect to surface morphology, phase composition and electrical properties [8]. Sulphuric acid is frequently used and yields porous oxide layer of certain thickness under PEO conditions [9][10][11][12][13]. Furthermore, previous studies also confirm the growth of a compact interlayer at the metal substrate which is thin compared to the porous layer [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies on PEO for medical applications, electrolytes with phosphoric acid (H 3 PO 4 ) have been frequently used, and oxide layers of comparable porosity and thickness can be formed [8][9][10]. Anatase is the dominant phase in these layers, and rutile is almost non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…Micro‐arc oxidation (MAO) is considered to be a convenient and effective technique to produce high‐quality ceramic coatings on Ti and its alloys . MAO is suitable to deposit over various substrates with complex geometries, and MAO‐derived coatings generally exhibit good bonding strength and thermal shock resistance . Wang et al have assessed the bonding strength and infrared emissivity properties of MAO coatings with TiO 2 and observed some general improvements of these 2 properties after applying a 2‐step MAO process.…”
Section: Introductionmentioning
confidence: 99%
“…11 MAO is suitable to deposit over various substrates with complex geometries, and MAO-derived coatings generally exhibit good bonding strength and thermal shock resistance. 12,13 Wang et al 14 have assessed the bonding strength and infrared emissivity properties of MAO coatings with TiO 2 and observed some general improvements of these 2 properties after applying a 2-step MAO process. In this particular type of 2-steps production, it is widely believed that the electrolyte composition can greatly influence the properties of the MAO coatings formed on titanium-based metals.…”
Section: Introductionmentioning
confidence: 99%